(untitled) (Scientific journal of the Fergana State University, 2023)
When nominating the oroobjects the religious beliefs, concept, objects and phenomena considered sacred, divine and exhibit a peculiar motivational feature. The article discusses similar phenomena in the examples of the oronims of Southern Uzbekistan.